A review on the role of novel adipokine Isthmin-1 and Subfatin in human type 2 diabetes mellitus - ahmed abed, Baydaa; Othman Farhan, Layla; Noori Salman, Isam; ehssan, safaa (University of Thi-Qar Journal of Science, 2023)
Adipokines are essential for maintaining cardiovascular and metabolic balance. The term "adipokines" refers to peptides in the pancreas, brain, vascular system, liver, immune system and muscle. adipokines regulate numbers of factors, such as energy expenditure, hunger, satiety, insulin sensitivity, and blood pressure, insulin secretion, adipogenesis and fat distribution, and that might make them play a role in future pharmacological treatment strategies for obesity and metabolic diseases. Isthmin-1 (Ism-1) is a recently discovered insulin-like adipokine that suppresses hepatic lipids. According to recent research, Ism-1 can enhance lipid metabolism and treat metabolic disorders linked to type 2 diabetic mellitus (T2DM). The primary source of the protein subfatin (SUB) is white adipose tissue. Subfatin (SUB) is expressed in these following tissues: adipose tissue, brain tissue, thymus gland, liver, activated human monocytes, spleen, omental adipose tissue, muscle, salivary glands and heart tissues. The SUB lowers insulin resistance to control glucose metabolism. Isthmian-1 is a novel biomarker for early management and diagnosis of T2DM and has a beneficial effect in glucose homeostasis and might be therapeutic for diabetes. Subfatin also plays a role in glucose metabolism and insulin sensitivity, so it has significant effect in pathogenesis and complication of diabetes.